The House by the Sea - Aspinall P. Patricia (Cambridge english readers Level 3)
A married couple, Carl and Linda Anderson, buy a weekend house by the sea. But one weekend Linda does not arrive at the house and Carl begins to worry. What has happened to her? Who is the taxi driver that follows Carl? And how much do the people in the village really know?